Flow and heat transfer of RP-3 aviation kerosene in horizontal tube at supercritical pressure under altered gravity levels. (5th May 2022) - Yu, Jia-Jia; Huang, Li; Sun, Shouli; Yu, Jin; Li, You-Rong
Highlights: Secondary flow and heat transfer at hypo- and hyper-gravity were analysed. Critical gravity levels for two kinds secondary flow evolution are 0.1 and 0.3g. Higher gravity level enhances heat transfer and exacerbates its uneven distribution. Higher heat flux accelerates secondary flow evolution and weakens heat transfer. Abstract: This paper presents a series of three-dimensional numerical simulations on the flow and heat transfer characteristics of the RP-3 aviation kerosene in a horizontal tube heated by different heat fluxes under altered gravity levels at the supercritical pressure. The RP-3 aviation kerosene with the initial temperature of 373 K flows in the horizontal tube heated by heat fluxes of 400 or 480 kW/m 2 with the mass velocity of 982.4 kg/(m 2 s). The results indicate that the evolution of the secondary flow pattern strongly depends on the gravity level. The critical gravity levels for the incipience of two kinds of the secondary flow pattern evolution along the main flow direction are 0.1g and 0.3g. The secondary flow enhanced by the gravity level promotes the local heat transfer on the inner wall near the bottom, while causes the heat transfer deterioration near the top of the horizontal tube. Moreover, the increase of the gravity level enhances the average heat transfer on the inner wall. The secondary flow pattern and tendencies of the turbulent kinetic energy are almost independent of the heat flux. However, higher heat flux accelerates the transition of the secondary flow patterns along the main flow direction and enlarges the local heat transfer difference between the top and the bottom. In addition, the heat transfer weakens with the increase of the heat flux.